Understanding the Integration of Physical and Human Geography in Chinese Academic Pursuits - Bao Jigang; Weng Shixiu (Redai dili, 2024)
The 21st century has seen an exponential growth in the number of papers published by Chinese geographers, yet this surge in publication has not corresponded to a commensurate increase in societal impact. The voices of geographers, particularly those of the younger generation, have diminished when confronted with substantial scientific and societal challenges. A pivotal factor contributing to this phenomenon is the academic evaluation system, which places significant emphasis on the quantities of papers and projects. This system significantly impedes cohesive progress in the field of Chinese geography, leading geographers, especially the younger generation, to diverge from the fundamental principles of the discipline. Consequently, there is a gradual neglect of the "comprehensiveness" and "regionality" dimensions that geography traditionally employs to tackle significant issues. To augment the capacity of geography to confront crucial challenges and enhance its standing within both the disciplinary and societal realms, Chinese geography should embark on a trajectory of consolidated development. This includes crucial steps such as strengthening geography education, establishing a leading problem-oriented framework, outlining pathways for integrating physical and human geography, and utilizing initiatives such as the "Top Ten Research Progresses in Chinese Geographical Science" to guide synthesized geographic development.